“Proyecto de factibilidad Técnico – económico para la instalación de una camal frigorífico en la provincia de San Martín - Díaz Díaz, Antonio (1997)
The present thesis is about a project of feasibility for the installation of a Camal refrigerator in the province of San Martin, of the Region of San Martin, which arises as a form of solve partly the problematic regional; normal supply of the contributing with red meat that he wont eat (beef and pork). Within this context is made the study of market starting by the potential livestock that is of 50,000 heads of cattle, and 32,100 heads level of all the Region San Martin, the takes is of 22% and 17% for cattle of swine percentage of and pigs respectively, the weight average of them covers in them carnal of Tarapoto is for cattle 145 Kg. and for pigs of 50 Kg. meat consumption represents 84% for cattle and 16% for swine, defined the size of the Camal refrigerator based on the: consumption growth which is 4.4%, to population growth which is 4.3% and per capita consumption which is 16.16 Gr...